2018
DOI: 10.1021/acs.joc.8b00488
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bromoundecyl Resorc[4]arenes and Applications of the Cone Stereoisomer as Selector for Liquid Chromatography

Abstract: As an extension of our studies on the multifaceted properties of C-alkylated resorc[4]arenes, we planned to immobilize on a solid support resorc[4]arenes with C-long side chains in the lower rim. To this purpose, we synthesized two conformationally diverse resorc[4]arenes containing a bromoundecyl moiety in the four axial pendants. The cone stereoisomer 6a (30% yield) was selected for the reaction with an aminopropylated silica gel (APSG) obtained from spherical Kromasil Si 100, 5 μm particles, to give the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…6,9 Importantly, they are chemically stable, structurally preorganized, easy to functionalize, and available in high purity and substantial quantities. 10,11 Recently, we designed and synthesized several resorc [4]arenes as supramolecular artificial linkers for oriented antibody immobilization. 12 In this previous work, we demonstrated that a gold surface plasmon resonance sensor chip surface modification by suitably functionalized resorc [4]arene macrocycles represents a potentially powerful system to improve sensitivity, providing new insight into sensor development.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 Importantly, they are chemically stable, structurally preorganized, easy to functionalize, and available in high purity and substantial quantities. 10,11 Recently, we designed and synthesized several resorc [4]arenes as supramolecular artificial linkers for oriented antibody immobilization. 12 In this previous work, we demonstrated that a gold surface plasmon resonance sensor chip surface modification by suitably functionalized resorc [4]arene macrocycles represents a potentially powerful system to improve sensitivity, providing new insight into sensor development.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most immobilizing approaches lead to a random orientation of Abs, resulting in lower binding site density and immunoaffinity. In this context, supramolecular chemistry has emerged as a suitable surface modification tool to allow the preorganization of artificial receptors and improve the functional properties of self-assembled monolayers (SAMs). Among the large pool of supramolecular macrocycles available, resorc[4]­arenes, belonging to the family of calixarenes, are characterized by a unique three-dimensional surface that can be functionalized at both the upper and lower rims with several functional groups to tailor their recognition properties toward a specific class of analytes. , Importantly, they are chemically stable, structurally preorganized, easy to functionalize, and available in high purity and substantial quantities. , Recently, we designed and synthesized several resorc[4]­arenes as supramolecular artificial linkers for oriented antibody immobilization . In this previous work, we demonstrated that a gold surface plasmon resonance sensor chip surface modification by suitably functionalized resorc[4]­arene macrocycles represents a potentially powerful system to improve sensitivity, providing new insight into sensor development .…”
Section: Introductionmentioning
confidence: 99%
“…Within the calixarene family, resorcinol-derived cyclic oligomers, namely resorc[4]arenes, endowed with cavities of molecular dimension, behave as an efficient artificial receptor [ 14 , 25 , 26 ]. The synthetic modularity and different complexation properties of the resorcarene-based macrocycles make them a promising building block for the design and synthesis of more sophisticated supramolecular architectures [ 27 , 28 , 29 , 30 , 31 ]. Efficient solubilizing agents were designed and developed by using several resorc[4]arenes [ 15 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The choice of the groups attached at the upper rim plays a pivotal role determining the shape, the rigidity and the complexation properties, whereas the functionalization of the lower rim is functional to surface anchoring. [26][27][28][29][30] Efficient sensor devices were designed and developed by using several resorcarene-based cavitands. [22] However, to date, limited use has been made of resorc [4]arene derivatives as an artificial linker for the site-directed antibody immobilization, giving rise to advanced immunosensors.…”
Section: Introductionmentioning
confidence: 99%